Eksplorasi Program Reintegrasi Sosial pada Warga Binaan di Lembaga Pemasyarakatan Narkotika - Asisah, Siti; -, Nurhayati (Social Welfare Study Program, 2017)
Social reintegration is the process of establishing new norms and values for people with social problems in prisons. This article discusses the understanding of how Social Reintegration Programs for Correctional Prisoners program, especially to drug cases. The research conducted using a qualitative descriptive approach. The primary data derived from interview results combined with other printed documents. The results of this study indicate that the Social Reintegration Program has a potential to play a role in reducing overcapacity in the prisons, but its implementation still requires development. In addition, there is still a negative stigma labelled by the community to the prisons inhabitants in addition to inadequate facilities, infrastructure and budget as well as a lack of skills owned by the targeted citizens when out of prisons. Keywords: General election, people with disabilities, disability rights, voters.